2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472007
|View full text |Cite
|
Sign up to set email alerts
|

A joint learning approach for cross domain age estimation

Abstract: We propose a novel joint learning method for cross domain age estimation, a domain adaptation problem. The proposed method learns a low dimensional projection along with a regressor, in the projection space, in a joint framework. The projection aligns the features from two different domains, i.e. source and target, to the same space, while the regressor predicts the age from the domain aligned features. After this alignment, a regressor trained with only a few examples from the target domain, along with more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Such non linear variations affect the accuracy of the facial representations. The studies in [89] , [95] and [14] indicate this problem and propose transfer learning and domain adaptation solutions to deal with it. A similar problem arises when performing age estimation across different expressions.…”
Section: Discussion On Age Estimationmentioning
confidence: 99%
“…Such non linear variations affect the accuracy of the facial representations. The studies in [89] , [95] and [14] indicate this problem and propose transfer learning and domain adaptation solutions to deal with it. A similar problem arises when performing age estimation across different expressions.…”
Section: Discussion On Age Estimationmentioning
confidence: 99%
“…Human ageing is determined by genes and influenced by intrinsic and extrinsic factors. Previous studies have demonstrated that ageing among populations is different and that learning age jointly with gender and/or ethnicity and/or expression is a more challenging task than learning age independently from these factors , Guo and Zhang (2014), Bhattarai at al. (2016), Georgopoulos et al ( 2018)).…”
Section: Cross-domain Age Estimationmentioning
confidence: 99%
“…Facial analysis is an important area of computer vision. The representative problems include face (identity) recognition [29], identity based face pair matching [30], age estimation [31], [32], kinship verification [33], emotion prediction [34], [35], among others. Facial analysis finds important and relevant real world applications such as human computer interaction, personal robotics, and patient care in hospitals [9], [10], [11], [36].…”
Section: Facial Analysismentioning
confidence: 99%